Mucocutaneous Manifestations in HIV/AIDS Patients - Hidayati, Afif Nurul; Harningtyas, Citra Dwi; Damayanti, Damayanti; Astari, Linda; Indramaya, Diah Mira; Listiawan, M. Yulianto; Utomo, Budi; Budiono, Budiono; Murtiastutik, Dwi; Widyantari, Septiana; Maylita Sari; Astindari, Astindari (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2021)
Background: The main target of human immunodeficiency virus (HIV) is cluster of differentiation 4 (CD4) T lymphocytes and several other immune cells that have CD4 receptors. They are also present in skin and mucosa, such as Langerhans cells (LC). Mucocutaneous lesions are one of the first clinical presentations of immunosuppression in HIV seropositive patients that manifest at different stages of the infection and require early diagnosis and prompt treatment. Purpose: To determine the clinical characteristics and the pattern of various mucocutaneous manifestations in Human immunodeficiency virus/Acquired immune deficiency syndrome (HIV/AIDS) patients at Intermediate Care and Infectious Diseases Dr. Soetomo General Academic Hospital Surabaya. Methods: This is a descriptive retrospective study with a cross-sectional design. The study subject was classified as all HIV-AIDS patients with mucocutaneous manifestations treated in Intermediate Care and Infectious Diseases Dr. Soetomo General Academic Hospital Surabaya in 2019. Result: Out of the 614 patients who participated in the study, 72.1% were males. The majority of patients were in the age group 25–49 years (75.4%). The most common risk factor was heterosexuality (41.7%). Based on the distribution of mucocutaneous manifestations, the most common mucocutaneous manifestation was candidiasis mucocutan 387 patients (49.4%) followed by the pruritic papular eruption (PPE) 118 patients (15.1%) and human papillomavirus infection 57 patients (7.3%). Conclusion: Mucocutaneous manifestations occur throughout the course of HIV infection, and they can be considered as good clinical indicators for the progression of the disease and underlying immune status in resource-poor settings.